Exergy Analysis of Transiant Modes in Hot Water Storages - Voloshchuk, Volodymyr; Nekrashevych, Olena; Liubytskyi, Serhii (Вісник Національного технічного університету «ХПІ». Серія: Енергетичнi та теплотехнiчнi процеси й устаткування, 2020)
The paper demonstrates the importance of taking into account the accumulation of exergy in a control volume of a thermal storage during transient modes for evaluation of exergy-based parameters. The investigations are based on the exergy balance equation and mathematical model of the mode of simultaneous thermal energy addition and removal. It is found that for the specified parameters of the unit, when the exergy accumulation is not included, the error of estimation of exergy-base parameters can be large: in case of calculation of fuel of exergy and exergy efficiency this error can reach 80 %, the exergy destruction values are received with 130 % error. It is shown that these errors depend on the ratio of rates of cold and hot working fluids and decrease with increasing this ratio, but almost do not depend on the storage volumes and the initial temperatures of working fluids. Including accumulation of exergy within the control volumes during dynamic modes of thermal systems is necessary for implementation of exergy-based control strategies.